2012
DOI: 10.1007/s00256-012-1534-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation with contrast-enhanced magnetic resonance imaging of the anterior cruciate ligament graft during its healing process: a two-year prospective study

Abstract: During the healing process the amount of revascularization tissue influences the MR imaging characteristics of the graft according to the examined site and the time interval after surgery. By 2 years postoperatively, revascularization completion coincides with the homogeneously low signal intensity of the graft, closely resembling native ACL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 35 publications
1
64
0
2
Order By: Relevance
“…Howell et al advocated the clinical relevance of graft signals on proton density-weighted imaging (PDWI), showing that intercondylar notch impingement resulted in increased graft intensity, and clinical outcomes were poorer when the high-intensity area exceeded N50% of the entire graft [8]. Ntoulia et al reported that MRI with a contrast agent such as gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA) clearly demonstrated that revascularization initiated from the periphery and progressed toward the center of the graft, which may explain part of the increment in graft intensity on conventional PDWI sequences [9,10]. Accordingly, graft intensity changes might reflect not only graft damage, but also neovascularization and matrix synthesis within the graft.…”
Section: Introductionmentioning
confidence: 98%
“…Howell et al advocated the clinical relevance of graft signals on proton density-weighted imaging (PDWI), showing that intercondylar notch impingement resulted in increased graft intensity, and clinical outcomes were poorer when the high-intensity area exceeded N50% of the entire graft [8]. Ntoulia et al reported that MRI with a contrast agent such as gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA) clearly demonstrated that revascularization initiated from the periphery and progressed toward the center of the graft, which may explain part of the increment in graft intensity on conventional PDWI sequences [9,10]. Accordingly, graft intensity changes might reflect not only graft damage, but also neovascularization and matrix synthesis within the graft.…”
Section: Introductionmentioning
confidence: 98%
“…If poor graft vascularization is persistent, some authors believe that this will eventually lead to early graft failure (graft failure within a year) or graft rupture. 31 This hypothesis is also supported by Ntoulia et al, 18 who reported that enhancement or neoangiogenesis of the intra-osseous osteoligamentous interface should persist throughout the first postoperative year and decrease after that. 18 If there is a decrease of enhancement within a year, there is a high possibility of disrupted or poor neoangiogenesis in the osteoligamentous interface.…”
Section: Discussionmentioning
confidence: 67%
“…21 Immediately after placement, the graft has uniformly low signal intensity, however, beginning in the next 3 months and peaking at 6 months posttransplant, there will be progressive neovascularization in the soft tissue surrounding the intra-articular portion of graft and at the osteoligamentous interface in the tunnels. 18,21,22 The ligamentization process causes an increase in signal intensity in T2WI images replacing the normal homogeneous low signal intensity of the graft tendon. 23 This ligamentization process can last up to 2 years with the graft returning to its original homogeneous low signal intensity at the end of the process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Press(In Press):e14060. 5 U n c o r r e c t e d P r o o f the entire course of the graft has been studied and it was shown that IGSI is a dynamic process of healing and by 2-years postreconstruction, the graft should resume uniformly low GSI on MRI (18,19 (2,20). In our study, IGSI of the IAP was observed in 36.6 %, and only 9.8% of patients showed low GSI of the entire graft course.…”
Section: Discussionmentioning
confidence: 74%